Digital Patriarchy and the Silencing of the Female Voice: A Critical Discourse Analysis of Hadith on Instagram - Nurul Hafizoh (Journal of Digital Islamic Thought, 2026)
This article interrogates the discursive construction of the female voice as ‘awrah within digital da’wah, specifically analyzing the Instagram account @thesunnah_path. Utilizing Norman Fairclough’s Critical Discourse Analysis (CDA), synthesized with the Mubādalah (reciprocity) hermeneutic, the study examines how religious authority and patriarchal ideologies are reproduced through social media. The analysis of text, discursive practices, and social structures reveals that theological terms such as fitnah (temptation) and obedience are instrumentalized to legitimize the domestication of women. This phenomenon represents a form of “digital patriarchy” that operates through language and algorithms to silence female agency. Conversely, the Mubādalah approach offers an egalitarian reinterpretation, positing the female voice as a medium for spiritual and intellectual expression rather than a source of moral corruption. Ultimately, this research underscores the urgency of deconstructing hegemonic narratives to restore gender justice and human-centric values to contemporary Islamic digital discourse.